Lower Limb Malrotation Is Regularly Present in Long-Leg Radiographs Resulting in Significant Measurement Errors - Maderbacher, Günther; Matussek, Jan; Greimel, Felix; Grifka, Joachim; Schaumburger, Jens; Baier, Clemens; Keshmiri, Armin (The Journal of Knee Surgery, 2019)
Weight-bearing long-leg radiographs are commonly used in orthopaedic surgery. Measured parameters, however, change when radiographs are conducted in different rotational positions of the leg. It was hypothesized that rotational errors are regularly present in long-leg radiographs resulting in wrong measurements. In 100 consecutive long-leg radiographs conducted according to the method of Paley, rotation was assessed by fibular overlap. Angular parameters in radiographs (mechanical lateral proximal femoral angle (mLPFA), mechanical lateral distal femoral angle (mLDFA), angle between the anatomical and mechanical femoral axis (AMA), mechanical medial proximal tibia angle (mMPTA), mechanical lateral distal tibial angle (mLDTA), and the mechanical femoral and tibial axis (mFA–mTA) were measured and deviations related to malrotation calculated. An average internal rotation of 8 degrees was found in lower limbs showing a range between 29 degrees of internal and 22 degrees of external rotation. As a result, mean differences before and after rotational correction for measured parameters (mLPFA, mLDFA, AMA, mMPTA, mLDTA, mFA–mTA) ranged between 0.4 and 1.7 degrees (−2.1; 5.6 95% confidence interval [CI]). In conclusion, malrotation of lower limbs is regularly present in long-leg radiographs. As all measured parameters are influenced by malrotation, correct lower limb rotation needs to be verified.
Keywords: long-leg radiographs; weight-bearing; mMPTA; mLDFA; mLPFA; mLDTA; rotation; rotational error; limb alignment; deformity